Prostacyclin Analogue–Loaded Nanoparticles Attenuate Myocardial Ischemia/Reperfusion Injury in Rats - Shin Yajima, MD, PhD (JACC: Basic to Translational Science, 2019)
Summary: Intravenously injected ONO-1301–containing nanoparticles (ONO-1301NPs), unlike an ONO-1301 solution, selectively accumulated in the ischemia/reperfusion (I/R)-injured myocardium of rats and contributed to the prolonged retention of ONO-1301 in the targeted myocardial tissue. In the ischemic area, proangiogenic cytokines were up-regulated and inflammatory cytokines were down-regulated upon ONO-1301NP administration. Consequently, ONO-1301NP–injected rats exhibited a smaller infarct size, better-preserved capillary networks, and a better-preserved myocardial blood flow at 24 h after I/R injury, compared with those in vehicle-injected or ONO-1301 solution–injected rats. ONO-1301NPs attenuate the myocardial I/R injury via proangiogenic and anti-inflammatory effects of the drug. Key Words: ischemia/reperfusion injury, nanoparticles, ONO-1301, prostacyclin